Al Qaeda's post 9/11 devolution: the failed jihadist struggle against the near and far enemy - Celso, Anthony N. (New directions in terrorism studies, 2015)
"This examination of Al Qaeda's decline since the 9/11 attacks focuses on the terror organization's mutation and fragmentation. It looks at its partnership with the local and regional jihadist networks that played a pivotal role in the Madrid, London, and Fort Hood attacks, arguing that, although initially successful, such alliances actually unraveled following both anti-terror policies and a growing rejection of violent jihadism in the Muslim world. Challenging conventional theories about Al Qaeda and homegrown terrorism, the book claims that jihadist attacks are now organized by overlapping international and regional networks that have become frustrated in their inability to enforce regime change and their ideological goals. The discussion spans the war on terror, analyzing major post 9/11 attacks, the failed jihadist struggle in Iraq, Al Qaeda's affiliates, and the organization's future prospects after the death of Osama Bin Laden and the Arab Spring. This assessment of the future of the jihadist struggle against Muslim governments and homegrown Islamic terrorism in the West will be an invaluable resource to anyone studying terrorism and Islamic extremism"--